Limb salvage surgery with endoprosthesis reconstruction in management of locally advanced primary bone tumours: a functional outcome evaluation - Sinha, Shashank Kumar; Das, Arijit; Das, Ayon; Ghosh, Sanjib (International Journal of Research in Orthopaedics, 2022)
Background: Endoprosthetic reconstruction using a custom-made metallic mega-endoprosthesis is one of the common modalities for limb salvage operation. The new promising advance of material science, design and fabrication of the endoprosthesis enable an immediate rehabilitation program and provide a durable and functional limb. The aim of the study was to evaluate the efficacy and functional outcome in patients with primary bone tumours treated by limb salvage surgery using endoprosthetic replacement. Methods: A total of 14 patients with primary bone tumour in major large joints of the body, selected between January 2019 to August 2020, were managed by limb salvage surgery via endoprosthetic replacement. This was a prospective study conducted at a Tertiary care Government Hospital in Kolkata, and all patients were followed up to a minimum of 1.5 years. The evaluation system used was proposed by Enneking, recommended by the musculoskeletal tumour society in addition to the radiologic evaluation. Results: At final follow-up, the mean musculoskeletal tumour society score was 89.71±3.58. The mean Knee Society Score of 9 patients was 85.55±3.64 and mean Harris hip score of 2 patients and Oxford shoulder score of 4 patients were 90.5 and 41.67 respectively by the end of 1.5 years. 12 (85.7%) patients did not have any complications. None of the cases had implant loosening or breakage, periprosthetic fracture, tumour recurrence or amputation. Conclusions: Endoprosthesis are excellent choices for the treatment of bone tumours with limb preservation in relation to pain, strength, and patient’s emotional acceptance as they reconstruct a limb with an acceptable oncologic, functional, and cosmetic result providing immediate weight-bearing capacity and generating a greater independence.